An unusual manifestation of Cardiac Sarcoidosis - Ramanathan, K; Platts, D; Apte, Yogesh V; Muthalidas, D (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Non tropical, non hypereosinophilic endo myocardial fibrosis has been reported in literature and is a rare entity. Cardiac Sarcoidosis manifesting as non-tropical, non hypereosinophilic endomyocardial fibrosis is unknown, though it classically affects the left ventricle and is not associated with specific risk factors. We describe an atypical presentation of sarcoidosis as non-tropical non hypereosinophilic endomyocardial fibrosis in a middle aged female who presented to us with refractory heart failure.